2012
DOI: 10.1074/jbc.m112.409300
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Structure of the Aquifex aeolicus Protein DUF752

Abstract: Background: Escherichia coli encodes a bifunctional oxidase/methyltransferase catalyzing the final steps of methylaminomethyluridine (mnm5U) formation in tRNA wobble positions.Results: Aquifex aeolicus encodes only a monofunctional aminomethyluridine-dependent methyltransferase, lacking the oxidase domain.Conclusion: An alternative pathway exists for mnm5U biogenesis.Significance: Information about how an organism modifies the wobble base of its tRNA is important for understanding the emergence of the genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
0
19
0
1
Order By: Relevance
“…We also reported the presence of cmnm 5 s 2 U and nm 5 s 2 U in total tRNA purified from an mnmC null mutant. However, it has been suggested that the formation of these intermediates is sensitive to growth conditions and specific strains, which might explain why they were not detected in other studies ( 23 , 26 , 41 ).…”
Section: Resultsmentioning
confidence: 83%
“…We also reported the presence of cmnm 5 s 2 U and nm 5 s 2 U in total tRNA purified from an mnmC null mutant. However, it has been suggested that the formation of these intermediates is sensitive to growth conditions and specific strains, which might explain why they were not detected in other studies ( 23 , 26 , 41 ).…”
Section: Resultsmentioning
confidence: 83%
“…The fact that B. subtilis MnmC-like activities reside in non MnmC homologous protein(s) calls for caution in assuming that cmnm 5 s 2 U may be the final modification in organisms lacking MnmC homologs. Moreover, the proposal that the ammonium pathway is responsible for the mnm 5 s 2 U synthesis in organisms that, like A. aeolicus [14], lack an MnmC(o) homolog, should be re-evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The ammonium pathway has been proposed to be the dominant route in Aquifex aeolicus because this species has a homolog of MnmC(m) but not of MnmC(o), and mnm 5 s 2 U, but not cmnm 5 s 2 U, has been HPLC-detected in bulk A. aeolicus tRNA hydrolysates [14]. Conversely, the glycine pathway has been considered the predominant route in Bacillus subtilis and Mycoplasma capricolum given that the genomes of both species lack the genes encoding the bifunctional MnmC protein or a monofunctional MnmC(m), and only cmnm 5 (s 2 )U(m)-type derivatives have been detected in certain MnmEG-substrate tRNAs (e.g., B. subtilis tRNA Lys UUU ) or bulk tRNA to date [1419]. Curiously back in the mid-1970s, Vold and colleagues reported the probable presence of mnm 5 s 2 U in B. subtilis tRNA [20,21] but they did not find evidence for this nucleoside in a subsequent study [16].…”
Section: Introductionmentioning
confidence: 99%
“…Putative orthologs of the E. coli bifunctional MnmC protein are conserved only in g-proteobacteria, but potential orthologs of a single domain have been identified in several genomes. 69,70 The phylogenetic analysis did not clear up whether the independent orthologs represent the ancestral or derived versions of the bifunctional MnmC enzyme. Nevertheless, the ability of the E. coli MnmC domains to function independently and to recognize different substrates suggests that the origin of the full MnmC protein present in g-proteobacteria likely happened by domain fusion.…”
Section: Function Of Modifications At the Wobble Uridinementioning
confidence: 99%